2018
DOI: 10.1111/inr.12460
|View full text |Cite
|
Sign up to set email alerts
|

Reaching for the stars: Iranian nurses’ perceptions of career success

Abstract: Future nurses could use these finding to reflect on their developed attributes throughout their studies and clinical placements and adjust their career preparation and learning to bridge any identified gaps. Organizational values and intervention for nursing staff could also be redesigned to align with the aspects of career success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 20 publications
4
55
0
4
Order By: Relevance
“…Career success refers to both the positive psychological feelings that individuals gradually accumulate and acquire in their work experience and work-related achievements (Zamanzadeh et al, 2019;Xin et al, 2020). Achieving career success is defined as developing individual potential, meeting the satisfaction of growth needs, and realizing individual selfvalue (Woolston, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Career success refers to both the positive psychological feelings that individuals gradually accumulate and acquire in their work experience and work-related achievements (Zamanzadeh et al, 2019;Xin et al, 2020). Achieving career success is defined as developing individual potential, meeting the satisfaction of growth needs, and realizing individual selfvalue (Woolston, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From the 2100 articles identified, we closely reviewed 17 for career success dimensions. Next, we created a test specification where we plotted the five domains identified in our previous study (Zamanzadeh et al 2019) and cross-checked these against those identified in the systematic review. This process did not reveal new dimensions.…”
Section: Study Settingmentioning
confidence: 99%
“…The progress of developing a multidimensional measure of career success has been slow due to the general lack of exploratory research with nurses (Li et al 2014). Encouragingly, Zamanzadeh et al (2019) interviewed nurses practicing in Iranian hospitals to understand how they perceived this concept. They found that nurses felt successful when they (1) provided high-quality care, (2) contributed to organizational objectives and worked collaboratively, (3) developed clinical skills, (4) showed important personal attributes and (5) felt internally satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses’ career adaptability is a kind of positive psychological resource that can help them adapt to the organizational environment quickly and make clear decisions in response to changes (Wei & Taormina, ). Nurses’ career adaptability can indirectly improve the flexibility of hospital management, help individuals achieve their career goals and increase their core competencies (Zamanzadeh et al, ). For improving career adaptability, prior research paid more attention to the supervisor and coworkers’ effects (Savickas, ).…”
Section: Introductionmentioning
confidence: 99%